Результаты экологического мониторинга приавтомагистральной территории автодороги «Киев-Ковель-Ягодин» М-07 - Голуб, Валентина Олександрівна; Волощинська, С. С.; Голуб, Сергій Миколайович; Голуб, Геннадій Сергійович; Holub, Valentyna O.; Voloshchynska, S. S.; Holub, Serhii M.; Holub, Hennadii S. (Брестский государственный технический университет, 2014)
It is discovered natural distribution of heavy metals in soils of motorway side’s zone of the road «Kyiv-Kovel-Yahotyn» depending on the distance of road-bed and windrose. It is determined a specific accumulative tendency to plants in respect of heavy metals. It is substantiated and recommended for plantations the plants’ assortment with the purpose of diminution the negative influence of pollutants on environment.
Keywords: миграция химических элементов; аккумуляция химических элементов; фоновое содержание свинца; «почва-растение»; урбанизация